Theoretical Aspects of Financial Support of Agricultural Enterprises in the Context of Modern Conditions - Serge KOLOTUKHA; Nataliia GVOZDEJ; Liudmyla CHVERTKO; Oksana VINNYTSKA; Tetiana KORNIIENKO (Communications of International Proceedings, 2020)
Theoretical approaches to the definition of the essence of the concept of «financial support» of an enterprise are presented, the evolution of this concept is traced. The economic content of the financial support of an agricultural enterprise is disclosed. The relationship between the category «financial security» and such categories as «financial stability» and «financial stability» is considered. It has been substantiated that the financial support of an agricultural enterprise characterizes such a state of financial resources, in which the enterprise can maneuver cash to ensure a continuous process of financial and economic activities, as well as renewal and expansion of its funds. It has been established that at present agricultural enterprises, in addition to their own and borrowed financial resources, use attracted financial resources. The modern forms of financial support of the reproduction process in the agricultural sector are determined.
Keywords: Financial Security; Financial Resources; Own And Borrowed Financial Resources; Agricultural Enterprises; Financial Stability; Financial Stability